Application of Autologous Bone Marrow Cell Mononuclears and Multipotent Mesenchymal Stromal Cells in the Treatment of Experimental Myocardial Infarction - Zhumagalikyzy, Saule; Kaulambaeva, Marzhan; Ahmetsadykov, Nurlan; Nurmuhambetova, Anar; Amirgazieva, Makpal; Ozbekov, Marlen; Bimenov, Kalbergen; Kozhaev, Askar; Fedotovskih, Galina; Shaymardanova, Galiya (Problems of Cryobiology and Cryomedicine, 2013)
N/A Probl Cryobiol Cryomed 2013; 23(3):271–274.